Effects of varus and sagittal implant positioning to the stress adaptation in cementless hip arthroplasty - Yusof, Muhammad Syahmi; Aznan, Nabila; Adull Manan, Nor Fazli; Marwan, Shahrul Hisyam; Mazlan, Muhammad Hazli; Abdul Halim Abdullah, Abdul Halim Abdullah (Penerbit UPM, 2021)
Total Hip Arthroplasty (THA) is one of the most common procedures in orthopedic surgery to treat the later stage of osteoarthritis. Implant mal-positioning is one of the risks that may lead to implant instability after surgery. The objective of this study to predict the effects of varus and sagittal positioning implant in promoting implant stability in cementless hip arthroplasty. Methods: Femoral bone (E=17 GPa, v=0.33) and titanium alloy (E=110 GPa, v=0.3) implant was considered in the analysis to represent the total hip arthroplasty. Various implant positions in varus and sagittal plane from -3° to 3° were modeled and analyzed for stair climbing activity. Results: The findings are discussed on the resulting maximum principal stress at the femoral bone and the implant. The stress variation in varus and sagittal cases are increased in the proximal and distal region where the cortical bone is bonded with the implant. The varus orientations show the severe stress concentration than sagittal orientations where the percentage increased up to 75% compared to normal conditions. Conclusion: The variation of implant position in varus and sagittal plane had influenced the stress distribution and contribute to bone adaptation and stress shielding effects. The effects of varus positioning were more significant compared to sagittal position in predicting the stress adaptation.